Patterns of Relations between Islam and the State in the Thought of a Liberal Islamic Network - Ihsan Maulana (Trigin Publisher, 2021)
The Laberal Islamic Network is an interesting phenomenon in Indonesia, because it is considered to break the establishment and slow thinking. This is understandable because the average JIL activist has a traditional Islamic background, which is oriented towards ubudiyah issues and dogmatic traditions, which practically must be followed without discussion, even though these rules are often irrelevant to the liberation of Muslims from poverty, ignorance or oppression. Liberal Islam is a particular form of interpretation of Islam with several foundations including, opening the door to ijtihad on all dimensions of Islam, they believe that ijtihad is the main principle for interpreting everything. Closing the door of ijtihad, either in a limited way or in its entirety, is a threat to Islam itself, because then Islam will experience decay. Liberal Islam believes that ijtihad can be carried out in all aspects, both in terms of muamalat (social interaction), ubudiyat (ritual) and divineyyat (theology). The purpose of JIL is to spread liberal Islamic ideas as widely as possible to the public, whether accepted or not accepted by the Indonesian people in particular, and abroad in general. create intellectual discourses on religious issues that are pluralist and democratic and have a gender perspective on campuses, print and electronic mass media with a more specific goal, namely, to provide alternative views for the people on socio-religious issues, so that they are not monopolized by one interpretation. anti-democratic and anti-pluralist and misogynist. Inviting the public to think critically, argumentatively, think contextually and not to be trapped in dogmatic values.